The Nutritional Content of Five Southwestern US Indigenous Maize (Zea Mays L.) Landraces of Varying Endosperm Type. Issue 2 (April 2022) - Oas, Sarah E.; Adams, Karen R.
Abstract : Any relative nutritional differences among the diverse maize ( Zea mays L.) landraces traditionally maintained in the Greater Southwest are little understood. In this article, we investigate a range of nutritional traits of five indigenous maize landraces in the US Southwest based on different kernel endosperm types: pop, flour, flint, dent, and sweet. We present macronutrient and micronutrient values for accessions of each landrace grown in the same environmental grow-out experiment. Macronutrient values vary considerably across these endosperm accessions. Sweet and flour maize had higher values of fat and protein, whereas dent had the highest carbohydrate content. Sweet and flour maize were comparatively the best sources of micronutrients. Sweet maize yielded the highest values of potassium, thiamin, and magnesium, and flour kernels had the highest riboflavin and niacin content. These results indicate that the maintenance of diverse maize landraces had nutritional as well as ecological, symbolic, and culinary value in both the past and today. Compared to modern commercial maize standards, traditional southwestern maize landraces had a somewhat higher caloric value, many had higher vitamin and mineral content, and all accessions but dent displayed higher protein values. This suggests that southwestern maize-focused diets that included diverse landraces may have been more nutritious than previously understood.